Effect of methane hydrate morphology on compressional wave velocity of sandy sediments: Analysis of pressure cores obtained in the Eastern Nankai Trough. (September 2015) - Konno, Yoshihiro; Jin, Yusuke; Yoneda, Jun; Kida, Masato; Egawa, Kosuke; Ito, Takuma; Suzuki, Kiyofumi; Nagao, Jiro
Abstract: Sediment cores containing methane hydrate were obtained under pressure from the Eastern Nankai Trough offshore Japan, and they have been analyzed to investigate the relationship between compressional wave velocity (P-wave velocity), methane hydrate saturation, and pore space hydrate morphology. P-wave velocities of pressure cores were measured at near in-situ pressures, thus preventing hydrate dissociation. After the measurement of P-wave velocity, the cores were cut, under pressure, into separate P-wave velocity intervals. Each core interval was depressurized while measuring the evolved gas volume to quantify methane hydrate saturation. The results show that P-wave velocity correlates well with hydrate saturation; the P-wave velocity varied from less than 1700 m/s in the hydrate-free section to greater than 2300 m/s in the section with the highest hydrate saturation of 72%. The measured P-wave velocities were correctly reproduced by the sediment frame component model by adjusting model parameters such as sand-clay ratio and effective stress. It was found that all core data plotted within the model predictions assuming zero effective stress and assuming in situ effective stress. This may indicate that the cores were in the process of relaxing from their in situ effective stress at the time of measurement. By using pressure cores and pressure core analysis technology, the relationship between P-wave velocity and methane hydrate saturation has been directly obtained nondestructively. The observed relationship in high-resolution core-scale specimens enables estimation of the hydrate morphology and is expected to be more accurate than cross-plot data in well logging. Highlights: Pressure core analysis technology was used for methane-hydrate-bearing natural cores. The relationship between P-wave velocity and methane hydrate saturation was analyzed. Hydrate morphology in pore space was determined as load-bearing. Relaxation of effective stress may affect P-wave velocity of pressure cores.